JANUBIY O‘ZBEKISTON SUDRALIB YURUVCHILARI PARAZITI – DIPLOPYLIDIUM NOELLERI (SKRJABIN, 1924) NING TARAQQIYOT SIKLI - Toshov U.J., Toshov U.J.; Vafoqulova M., Vafoqulova M. (Actual problems and prospects of the study of the fauna, 2024)
Research work was carried out in 2020-2024 in order to study the development cycle of cestodes (Cestoda Rudolphi, 1809) reptiles of Southern Uzbekistan. The developmental cycle of the helminth Diplopylidium noelleri (Skrjabin, 1924) belonging to the family Diplidiidae (Mola, 1929) of the class Cyclophylillidea (Beneden in Braun, 1900) of the class Cestoda (Rudolphi, 1809) was studied. The development cycle of Diplopylidium noelleri takes place with the participation of the intermediate host - beetles and the reservoir host - representatives of the geckos (Gekkonidae), agamidae (Agamidae), lizards (Lacertidae) family of reptiles.